Outcomes, infectiousness, and transmission dynamics of patients with extensively drug-resistant tuberculosis and home-discharged patients with programmatically incurable tuberculosis: a prospective cohort study. Issue 4 (April 2017) - Dheda, Keertan; Limberis, Jason D; Pietersen, Elize; Phelan, Jody; Esmail, Aliasgar; Lesosky, Maia; Fennelly, Kevin P; te Riele, Julian; Mastrapa, Barbara; Streicher, Elizabeth M; Dolby, Tania; Abdallah, Abdallah M; et al.
Summary: Background: The emergence of programmatically incurable tuberculosis threatens to destabilise control efforts. The aim of this study was to collect prospective patient-level data to inform treatment and containment strategies. Methods: In a prospective cohort study, 273 South African patients with extensively drug-resistant tuberculosis, or resistance beyond extensively drug-resistant tuberculosis, were followed up over a period of 6 years. Transmission dynamics, infectiousness, and drug susceptibility were analysed in a subset of patients from the Western Cape using whole-genome sequencing (WGS; n=149), a cough aerosol sampling system (CASS; n=26), and phenotypic testing for 18 drugs (n=179). Findings: Between Oct 1, 2008, and Oct 31, 2012, we enrolled and followed up 273 patients for a median of 20·3 months (IQR 9·6–27·8). 203 (74%) had programmatically incurable tuberculosis and unfavourable outcomes (treatment failure, relapse, default, or death despite treatment with a regimen based on capreomycin, aminosalicylic acid, or both). 172 (63%) patients were discharged home, of whom 104 (60%) had an unfavourable outcome. 54 (31%) home-discharged patients had failed treatment, with a median time to death after discharge of 9·9 months (IQR 4·2–17·4). 35 (20%) home-discharged cases were smear-positive at discharge. Using CASS, six (23%) of 26 home-discharged cases with data available expectorated infectious culture-positive cough aerosols in the respirable range (<5 μm), and most reported inter-person contact with suboptimal protective mask usage. WGS identified 17 (19%) of the 90 patients (with available sequence data) that were discharged home before the diagnosis of 20 downstream cases of extensively drug-resistant tuberculosis with almost identical sequencing profiles suggestive of community-based transmission (five or fewer single nucleotide polymorphisms different and with identical resistance-encoding mutations for 14 drugs). 11 (55%) of these downstream cases had HIV co-infection and ten (50%) had died by the end of the study. 22 (56%) of 39 isolates in patients discharged home after treatment failure were resistant to eight or more drugs. However, five (16%) of 31 isolates were susceptible to rifabutin and more than 90% were likely to be sensitive to linezolid, bedaquiline, and delamanid. Interpretation: More than half of the patients with programmatically incurable tuberculosis were discharged into the community where they remained for an average of 16 months, were at risk of expectorating infectious cough aerosols, and posed a threat of transmission of extensively drug-resistant tuberculosis. Urgent action, including appropriate containment strategies, is needed to address this situation. Access to delamanid, bedaquiline, linezolid, and rifabutin, when appropriate, must be accelerated along with comprehensive drug susceptibility testing. Funding: UK Medical Research Council, South African Medical Research Council, South African National Research Foundation, European & Developing Countries Clinical Trials Partnership, Oppenheimer Foundation, Newton Fund, Biotechnology and Biological Sciences Research Council, King Abdullah University of Science & Technology.